Cover Picture: Expedient Synthesis of Bridged Bicyclic Nitrogen Scaffolds via Orthogonal Tandem Catalysis (Angew. Chem. Int. Ed. 40/2021). Issue 40 (28th July 2021) - Biswas, Sovan; Van Steijvoort, Ben F.; Waeterschoot, Marjo; Bheemireddy, Narendraprasad Reddy; Evano, Gwilherm; Maes, Bert U. W.
Abstract : Escape from flatland . Increased saturation (fraction of sp 3 ) is more likely to be successful when moving compounds through the drug development pipeline. Bridged nitrogen heterocycles have a huge potential in drug discovery, although long synthetic sequences are typically required. New step‐economic and selective organic syntheses are therefore highly sought after. Bert U. W. Maes et al. describe in their Research Article on page 21988 the synthesis of the normorphan skeleton through challenging tandem catalysis. Cover design by Joris Snaet.